KEBERADAAN HUKUM WARIS ADAT DALAM PEMBAGIAN WARISAN PADA MASYARAKAT ADAT BATAK TOBA SUMATERA UTARA - Aisyah Aisyah; Novia Alexia (MIZAN, Jurnal Ilmu Hukum, 2022)
The Toba Batak community adheres to a patrilineal inheritance system which has the basis that children inherit their father on the condition that those who are truly considered the heirs of their fathers are sons, while female children for daughters inherit from their mother's assets. at the time of her previous marriage. This research is a juridical legal research. Data collection used secondary data in the form of references and reports on the distribution of Toba Batak traditional inheritance. Data analysis using literature study and field research were analyzed descriptively qualitatively. The results showed that the distribution of Toba Batak traditional inheritance adheres to the patrilineal system / father's line, where the eldest and youngest sons get their rights, but the second and second children of the youngest children and women are not heirs. The distribution of inheritance assets has undergone a shift in urban communities. In general, people who live in rural areas still apply a system of patrialism (prioritizing boys as successors). The national law on inheritance based on the Civil Registry provides that the distribution of inheritance from the parents, both boys and girls, get the same share.